A student affairs podcast as novel communication tool - Frayha, Neda; Brown, Jessica; Parker, Donna (Canadian Medical Education Journal, 2019)
Podcasts are prevalent within medical education, but not within medical student affairs. Our Office of Student Affairs (OSA) created a podcast focusing on topics relevant to the medical student experience. There have been over 20,000 downloads thus far. Survey responses and feedback have been positive and highlight the podcast’s utility as a communication tool, with 96% of respondents saying they would recommend this podcast to others. Given the mission of student affairs offices to advise, mentor, and educate students, a student affairs podcast is an exciting innovation for medical schools to consider.